Oligometastases from prostate cancer: Local treatment with stereotactic body radiotherapy (SBRT) - Habl, Gregor; Straube, Christoph; Schiller, Kilian; Duma, Marciana Nona; Oechsner, Markus; Kessel, Kerstin A.; Eiber, Matthias; Schwaiger, Markus; Kuebler, Hubert; Gschwend, Juergen E.; Combs, Stephanie E. (BMC Cancer, 2017)
Background: The impact of local tumor ablative therapy in oligometastasized prostate cancer (PC) is still under debate. To gain data for this approach, we evaluated oligometastasized PC patients receiving stereotactic body radiotherapy (SBRT) to bone metastases. Methods: In this retrospective study, 15 oligometastasized PC patients with a total of 20 bone metastases were evaluated regarding biochemical progression-free survival (PSA-PFS), time to initiation of ADT, and local control rate (LCR). Three patients received concomitant androgen deprivation therapy (ADT). Results: The median follow-up after RT was 22.5 months (range 7.0-53.7 months). The median PSA-PFS was 6.9 months (range 1.1-28.4 months). All patients showing a decrease of PSA level after RT of at least factor 10 reveal a PSA-PFS of >12 months. Median PSA-PFS of this sub-group was 23.1 months (range 12.1-28.4 months). Local PFS (LPFS) after 2 years was 100%. One patient developed a local failure after 28.4 months. Median distant PFS (DPFS) was 7.36 months (range 1.74-54.34 months). The time to initiation of ADT in patients treated without ADT was 9.3 months (range 2.6-36.1 months). In all patients, the time to intensification of systemic therapy or the time to initiation of ADT increased from 9.3 to 12.3 months (range 2.6-36.1 months). Gleason-Score, ADT or the localization of metastasis had no impact on PFS or time to intensification of systemic therapy. No SBRT related acute or late toxicities were observed. Conclusion: Our study shows that SBRT of bone metastases is a highly effective therapy with an excellent risk-benefit profile. However, PFS was limited due to a high distant failure rate implying the difficulty for patient selection for this oligometastatic concept. SBRT offers high local cancer control rates in bone oligometastases of PC and should be evaluated with the aim of curation or to delay modification of systemic treatment.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Individualized radiotherapy; Oligometastases; Prostate cancer; PSA; PSMA-PET; SBRT